Integrating sports psychiatry in the interdisciplinary care of elite sports teams <subtitle>A conceptual model</subtitle> - Armaan Zaré; Todd Stull (Hogrefe AG, 2023)
Abstract: Introduction: Sports psychiatry is a developing field whose focus is the diagnosis, treatment, and management of mental illness in sports team members. Participation in elite sports can compromise mental health as psychiatric symptoms and disorders are often unrecognized until players experience performance failures, injury, or interpersonal concerns. Despite the growing recognition of psychiatric illness in sports, sports psychiatry is yet to be widely practiced in athlete healthcare management. Methods: We conducted a search on relevant publications on sports psychiatry and mental health in elite athletes. Results: Numerous papers detailed mental health statistics in elite athletes as well as outlined the development of sports psychiatry with respect to healthcare management. The papers describe cultural barriers to athlete mental health treatment include stigma, low mental health literacy, adverse mental health treatment experiences, busy schedules, and cultural/religious factors. Modifiable systemic factors include conflicts of interest for team clinicians caused by dual loyalty to sports franchises, and power relations encompassing intra-team hierarchies that prevent both help-seeking behaviors and the disclosure of harassment. Conclusion: The proposed model recommends that sports leagues and tournament organizations hire sports psychiatrists to monitor the standard of care provided within each sports franchise as a quality control initiative to incentivize sports franchises to offer the highest-level of healthcare, combating conflicts of interest and harassment. The conceptual model recommends each sports franchise integrate sports psychiatrists onsite with elite sports team members with the long-term goal of achieving SAMHSA's full integration model pending available funding and sports culture shifts.